Pengembangan LKPD Fisika Berbasis Etnosains untuk Meningkatkan Hasil Belajar Kognitif Siswa pada Materi Gelombang Bunyi - Muliani, Muliani; Hasmi Br Lembong; Halimatus Sakdiah; Nuraini Fatmi; Nanda Novita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study was to determine the feasibility of Physics LKPD based on ethnoscience and to determine the increase in students' cognitive learning outcomes after using Physics LKPD based on ethnoscience. This study used the research and development (R&D) method with the ADDIE model. The sample used in this study was 2 classes, namely class XI IPA 1 and class XI IPA 2, totaling 37 students. Data collection techniques using questionnaires, tests, and validation sheet instruments from media experts, material experts, and teacher experts. The results of the study obtained from the results of the material expert validator obtained a percentage score of 87% with the criteria of